Security Framework for Agent-Based Cloud Computing - Venkateshwaran, K.; Malviya, Anu; Dikshit, Utkarsha; Venkatesan, S. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Agent can play a key role in bringing suitable cloud services to the customer based on their requirements. In agent based cloud computing, agent does negotiation, coordination, cooperation and collaboration on behalf of the customer to make the decisions in efficient manner. However the agent based cloud computing have some security issues like (a.) addition of malicious agent in the cloud environment which could demolish the process by attacking other agents, (b.) denial of service by creating flooding attacks on other involved agents. (c.) Some of the exceptions in the agent interaction protocol such as Not-Understood and Cancel_Meta protocol can be misused and may lead to terminating the connection of all the other agents participating in the negotiating services. Also, this paper proposes algorithms to solve these issues to ensure that there will be no intervention of any malicious activities during the agent interaction.
Keywords: agents; cloud computing; security; service capability; IJIMAI